2019
DOI: 10.1111/joor.12808
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and intra‐operative factors affecting the outcome of arthrocentesis in disc displacement without reduction: A retrospective study

Abstract: Background Temporomandibular disorder (TMD) is a group of disease which affects the temporomandibular joint (TMJ) and supporting tissues of the musculoskeletal structures. Arthrocentesis is an effective treatment modality for TMD, especially in patients who suffer from pain and limited mouth opening. Objective The aim of this study was to investigate the effects of pre‐operative and intra‐operative variables on the clinical outcome of arthrocentesis therapy. Methods The records of 83 patients diagnosed as disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 30 publications
3
7
0
6
Order By: Relevance
“…In our study, there was the prevalence of the female sex among patients, which was corroborated by the findings of several studies. 10,[17][18][19][20][21][22] In the present study, a mean age of patients of 32.2 years (16-61) was shown, which coincided with 2 studies that found a mean age of 20 to 40 years. 10,14,17,21,22 Although TJDS span all age groups, they generally affect the age-range from young people to middle-aged adults.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, there was the prevalence of the female sex among patients, which was corroborated by the findings of several studies. 10,[17][18][19][20][21][22] In the present study, a mean age of patients of 32.2 years (16-61) was shown, which coincided with 2 studies that found a mean age of 20 to 40 years. 10,14,17,21,22 Although TJDS span all age groups, they generally affect the age-range from young people to middle-aged adults.…”
Section: Discussionsupporting
confidence: 92%
“…10,[17][18][19][20][21][22] In the present study, a mean age of patients of 32.2 years (16-61) was shown, which coincided with 2 studies that found a mean age of 20 to 40 years. 10,14,17,21,22 Although TJDS span all age groups, they generally affect the age-range from young people to middle-aged adults. 23 In the study of Dimitroulis (2015), the mean age was 47.2 (SD: 15.1).…”
Section: Discussionsupporting
confidence: 92%
“…Nishimura et al [ 25 ] described the MMO value of more than 38 mm, and mild or no pain scores were counted as successful procedures in their study. Bas et al [ 26 ] accepted the MMO value of more than 35 mm and VAS pain scores of lower than 3 were accepted as successful at the 3 rd month follow-up in their study. When considered the success rate of pain and MMO values independently, it was assessed as 91% and 79.5%, respectively.…”
Section: Discussionmentioning
confidence: 98%
“…The efficiency of this process is accentuated by the vacuum pump, that also promotes other benefits already mentioned. Also, it can possibly reduce the risk of extravasation of solution used during irrigation, that already has been associated with a negative effect on the success of the procedure 16 .…”
Section: Discussionmentioning
confidence: 99%